Power conversion for a novel AC/DC aircraft electrical distribution system - Trentin, Andrew; Zanchetta, Pericle; Wheeler, Patrick; Clare, Jon C. (Institution of Engineering and Technology, 2014)
This paper proposes a novel and compact AC/DC electrical distribution system for new generation aircraft. In these new aircraft power systems, all loads are fed by two dc bus systems: at 28V and at +/-270V. The electrical distribution system, whose design and implementation are described in this paper, has only one primary AC source (360-900Hz at 230V) with all the required dc voltage levels being derived from this source. This solution enables elimination of the complex mechanical coupling apparatus currently used, for fixed frequency AC systems, to maintain the generator speed at constant level while the engines operate at variable speed. Under the proposed solution, all conversion stages needed to generate the various output voltage levels are implemented using power converters assembled in one unit. Each converter has a current control loop in order to regulate the output current even during output line short circuits and also to limit the inrush current to the circuit at turn-on. To prove the concept a 5 kW prototype was designed and tested, and demonstrated to meet all the specifications within relevant standards regarding input and output power quality.